MANAGING CHANGE IN IMPLEMENTING THE COMPUTERISED SYSTEM FOR SOCIAL WORK PRACTITIONERS IN GAUTENG - Phatudi, Tebogo Talitha (My University, 2011)
The evolution of the social work profession is of such a nature that more emphasis is put on soft skills like listening, communication, problem-solving, empathy, among others; hence their dependence on paper-based systems for keeping of records on the services rendered in performing their day-to-day duties. The literature reviewed revealed that the use of computer systems in the social work field of practice remains relatively unknown. After the 1994 democratic dispensation, there has been a growing demand for sound, cost-effective management practices in the South African context; hence the social work profession was not excluded from applying the available technology tools to enhance cost-effective service delivery to the benefit of the vulnerable communities. The research aimed at examining the efficacy and flaws in the management styles and strategies employed in managing the resistance towards the transformation introduced through the implementation of the computerised system in the public sector organisation using a change management case study. Academic debates underpinned strong top management support as an imperative for implementing change management initiatives. The research revealed that no single management style is a „one-size-fits-all‟ but that a combination of management styles challenged the status quo by placing all affected practitioners at disequilibrium and compelled them to embrace the transformation. Furthermore, management had to some extent succeeded in persuading the practitioners in considering the organisational vision and goals above their self-interest as reflected in their values, beliefs and attitudes. The change management processes adopted promoted transparency and iii instilled a culture of participation and commitment towards improved performance and service delivery by reducing the turnaround times.
MM thesis - P&DM
Keywords: Social workers, Gauteng; Change management